THE ANALYSIS OF SEXUAL CONSENT RULES IN ARTICLE 5 OF PERMENDIKBUD RISTEK NUMBER 30 OF 2021 REVIEWED FROM THE PERSPECTIVE OF ISLAMIC LAW - Surjanti Surjanti; Yudi Setiyono; Widowati Widowati; Retno Sari Dewi; David Budi Laksono (Universitas Dharma Wacana, 2022)
Regarding the treatment of sexual violence (PPKS) in tertiary institutions, the government released PERMENDIKBUD RISTEK No. 30 of 2021. However, that does not imply that this ministerial regulation is without flaws or shortcomings. The phrase